"Self-degradation" of 2-chlorophenol in a sequential cathode-anode cascade mode bioelectrochemical system. (1st November 2021) - Yang, Kaichao; Zhao, Yingxin; Zhou, Xu; Wang, Qian; Pedersen, Thomas Helmer; Jia, Zhichao; Cabrera, Jonnathan; Ji, Min
Highlights: Developed double-chamber BES to simultaneously degrade cathode 2-CP and anode phenol. Optimum concentration of anode acetate and phenolic compounds were investigated. Sequential cathode-anode mode was designed for 2-CP dechlorination and ring-cleavage. Critical operating parameters (applied voltage and pH) were optimized. Analyses showed that bioanodes played a decisive role in BES performance. Abstract: A sequential cathode-anode cascade mode bioelectrochemical system (BES) was designed and developed to achieve the "self-degradation" of 2-chlorophenol (2-CP). With the cooperation of cathode and anode, the electrons supplied for the cathode 2-CP dechlorination come from its own dechlorinated product in the anode, phenol. Separate degradation experiments of cathode 2-CP and anode phenol were firstly conducted. The optimum concentration ratio of anode acetate to phenolic compound (3.66/1.56) and the phenolic compound degradation ability of BES were investigated. With the formation of the bioanode able to degrade phenol, the sequential cathode-anode cascade mode BES was further developed, where 2-CP could achieve sequential dechlorination and ring-cleavage degradation. When applied voltage was 0.6 V and cathode influent pH was 7, 1.56 mM 2-CP reached 80.15% cathode dechlorination efficiency and 58.91% total cathode-anode phenolic compounds degradation efficiency. The bioanodes played a decisive role in BES. Different operating conditions would affect the overall performance of BES by changing the electrochemical activity and microbial community structure of the bioanodes. This study demonstrated the feasibility of the sequential cathode-anode cascade mode BES to degrade 2-CP wastewater and provided perspectives for the cooperation of cathode and anode, aiming to explore more potential of BES in wastewater treatment field. Graphical abstract: Image, graphical abstract